THE ROLE OF THE CREATIVE INDUSTRY: EMPIRICAL STUDY OF AHA COFFEE SHOPS ON THE GROWTH OF MSMES IN INDONESIA - Vina Rahmayanti; Setiyo Purwanto (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Coffee Shop is one of the MSME-based creative industries that is growing very rapidly in Indonesia. This business management uses literature-based business concepts taken from research meta data. So this research aims to examine the influence of total quality management (TQM), implementing technology (IT) and organizational culture (OC) on managerial performance (MP) at AHA Coffee Shop. The method used in this research uses descriptive quantitative. The population in this study were all employees and customers who were registered as members at AHA Coffee Shop and the total sample taken was 104 respondents. The statistical tool used to process research data uses the SPSS statistical application program. Where the results of statistical data processing show that the variables TQM, AT and OC partially and simultaneously have a significant effect on MP at AHA Coffee Shop.